2020
DOI: 10.3390/ph13090224
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum Ethanol Extracts Enhance Re-Epithelialization and Prevent Keratinocytes from Free-Radical Injury

Abstract: Ganoderma lucidum or Reishi is recognized as the most potent adaptogen present in nature, and its anti-inflammatory, antioxidant, immunomodulatory and anticancer activities are well known. Moreover, lately, there has been an increasing interest from pharmaceutical companies in antiaging G. lucidum-extract-based formulations. Nevertheless, the pharmacological mechanisms of such adaptogenic and regenerative actions remain unclear. The present investigation aimed to explore its molecular and cellular effects in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 43 publications
0
17
0
2
Order By: Relevance
“…When the confluent cells formed a homogeneous carpet and a vertical wound in the wells using a 200 µL tip was performed, culture medium containing HT at 1, 5, and 10 µM or the vehicle alone was added to the wells, after two washes to eliminate the cells detached. The wound area was recorded immediately and after 18 h through microscope analysis, as previously described [ 69 ] and quantified by Wimasis Image Analysis software (Onimagin Technologies Spa, Cordoba, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…When the confluent cells formed a homogeneous carpet and a vertical wound in the wells using a 200 µL tip was performed, culture medium containing HT at 1, 5, and 10 µM or the vehicle alone was added to the wells, after two washes to eliminate the cells detached. The wound area was recorded immediately and after 18 h through microscope analysis, as previously described [ 69 ] and quantified by Wimasis Image Analysis software (Onimagin Technologies Spa, Cordoba, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…H 2 O 2 induced cytotoxicity dose-dependently, starting at 50 µM, where the inhibition of cell viability was statistically significant, and reaching a reduction of 29.1% at 200 µM. Previous studies reported that lower concentrations of H 2 O 2 (≤250 µM) induced apoptotic cell death of more cells, whereas higher H 2 O 2 concentrations (1000 µM) resulted in an increase in overall cell death but a reduction in apoptosis [28,29]. Therefore, we decided to use 200 µM of H 2 O 2 in the subsequent experiments.…”
Section: Mangostanin Reverts and Prevents Cytotoxicity Induced By H 2...mentioning
confidence: 93%
“…The CHCl3 and MeOH extracts of G. mangostana arils (1 Ext CHCL3 and 1 Ext MeOH) and shells (2 Ext CHCL3 and 2 Ext MeOH) were further purified by HPLC-UV to afford compounds 1-12 (Figure 1). The chloroform and methanol extracts of mangosteen arils submitted to purification by HPLC-UV showed a similar profile characterized by the occurrence of five main compounds, identified as 1,7-dihydroxy-3-methoxy-2-(3-methylbut-2-enyl)xanthen-9-one (1), 1,3,7-trihydroxy-2,8-bis(3-methyl-2-buten-1-yl)-9H-xanthen-9one (2), α-mangostin (3), demethylcalabaxanthone (4), and mangostanin (5), also known as 6-hydroxycalabaxanthone or 9-hydroxycalabaxanthone [2,28,29]. The chloroform extract of mangosteen shells submitted to purification by HPLC-UV allowed the isolation of mangostanol (6), garcinone D (7), γ-mangostin (8), gudraxanthone (9), 8-deoxygartanin (10), garcinone E (11), β-mangostin (12), along with compounds 2, 3 and 5.…”
Section: Extraction Characterization and Purification Of Twelve Compo...mentioning
confidence: 99%
“…Its orally given extracts improved hematological parameters in healthy rats; researchers saw a slight but significant increase in hemoglobin levels and a great rise in leukocyte numbers [196]. This could be probably explained by a combination of positive effects of Ganoderma iron content and its antioxidant and anti-inflammatory properties [197,198].…”
Section: Superfoods As Nutritional Strategies For Iron Level Replenismentioning
confidence: 99%